1995
DOI: 10.1001/archinte.1995.00430100105012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Antihypertensive Agents on Proteinuria and Renal Function

Abstract: Long-term beneficial effects of antihypertensive agents on proteinuria and glomerular filtration rate are proportional to blood pressure reductions and are similar in diabetic and nondiabetic patients with renal disease. In addition, angiotensin-converting enzyme inhibitors, and possibly nondihydropyridine calcium antagonists, have additional beneficial effects on proteinuria that are independent of blood pressure reductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(97 citation statements)
references
References 80 publications
3
89
1
4
Order By: Relevance
“…In this study, BP was remarkably reduced by nitrendipine, which might have accounted for its anti-albuminuric effect. This observation is consistent with previous reports that BP control is an important factor in reducing UAE in hypertensive patients with both incipient and overt nephropathy 3,5,24,41,42 ; and (b) second, the late effect of nitrendipine on UAE, which resembles our previous observation with another dihydropyridine CCB, amlodipine, 23 suggests that the duration of follow-up of intervention trials must be sufficiently long in order to fully detect the drug effect on UAE.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, BP was remarkably reduced by nitrendipine, which might have accounted for its anti-albuminuric effect. This observation is consistent with previous reports that BP control is an important factor in reducing UAE in hypertensive patients with both incipient and overt nephropathy 3,5,24,41,42 ; and (b) second, the late effect of nitrendipine on UAE, which resembles our previous observation with another dihydropyridine CCB, amlodipine, 23 suggests that the duration of follow-up of intervention trials must be sufficiently long in order to fully detect the drug effect on UAE.…”
Section: Discussionsupporting
confidence: 92%
“…ACE inhibitors appear to reduce albumin excretion more than other agents, but their effect on glomerular filtration rate appears to be similar. 47 Although hypertensive microalbuminuric type 2 diabetic patients should be treated according to standard criteria to reduce their risk of cardiovascular disease, there is no firm evidence to suggest that antihypertensive treatment of normotensive microalbuminuric individuals with type 2 diabetes reduces progression to renal failure or cardiovascular disease. There is, however, some evidence to suggest that intensified multifactorial intervention in microalbuminuric type 2 diabetic patients can reduce the progression to overt nephropathy.…”
Section: Questions Not Answered By the Recent Studiesmentioning
confidence: 99%
“…In two metaanalyses, long-term beneficial effects of antihypertensive agents on proteinuria were proportional to blood pressure reductions and ACE inhibitors and possibly non-dihydropyridine (non-DHP) calcium antagonists have additional beneficial effects that are independent of blood pressure reductions. 10,11 Studies with non-DHP calcium antagonists in diabetic nephropathy demonstrated that beneficial effects in the rate of decline of renal function were comparable with the effects of ACE inhibitors. 12,13 ACE inhibitors improve glucose use and insulin sensitivity in hypertensive patients with type 2 diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%